Return to work after COVID-19 infection – A Danish nationwide registry study. (February 2022) - Jacobsen, P.A.; Andersen, M.P.; Gislason, G.; Phelps, M.; Butt, J.H.; Køber, L.; Schou, M.; Fosbøl, E.; Christensen, H.C.; Torp-Pedersen, C.; Gerds, T.; Weinreich, U.M.; et al.
Abstract: Objectives: This study aimed to explore return to work after COVID-19 and how disease severity affects this. Study design: This is a Nationwide Danish registry–based cohort study using a retrospective follow-up design. Methods: Patients with a first-time positive SARS-CoV-2 polymerase chain reaction test between 1 January 2020 and 30 May 2020, including 18–64 years old, 30-day survivors, and available to the workforce at the time of the first positive test were included. Admission types (i.e. no admission, admission to non–intensive care unit [ICU] department and admission to ICU) and return to work was investigated using Cox regression standardised to the age, sex, comorbidity and education-level distribution of all included subjects with estimates at 3 months from positive test displayed. Results: Among the 7466 patients included in the study, 81.9% (6119/7466) and 98.4% (7344/7466) returned to work within 4 weeks and 6 months, respectively, with 1.5% (109/7466) not returning. Of the patients admitted, 72.1% (627/870) and 92.6% (805/870) returned 1 month and 6 months after admission to the hospital, with 6.6% (58/870) not returning within 6 months. Of patients admitted to the ICU, 36% (9/25) did not return within 6 months. Patients with an admission had a lower chance of return to work 3 months from positive test (relative risk [RR] 0.95, 95% confidence interval [CI] 0.94–0.96), with the lowest chance in patients admitted to an ICU department (RR 0.54, 95% CI 0.35–0.72). Female sex, older age, and comorbidity were associated with a lower chance of returning to work. Conclusion: Hospitalised patients with COVID-19 infection have a lower chance of returning to work with potential implications for postinfection follow-up and rehabilitation.